THEORETICAL ASPECTS OF THE USE OF DIDACTIC PRINCIPLES IN BILINGUAL TRAINING MASTERS - Ekaterina A. Klushina (Вестник Северо-Кавказского федерального университета, 2022)
The article analyzes the definition of «bilingual training». It presents the author’s interpretation of this phenomenon. The article considers the didactic principles of bilingual training, analyzes their role in the process of forming master’s abilities in bilingual intercultural communication mode.